2011
DOI: 10.1007/s00384-011-1374-6
|View full text |Cite
|
Sign up to set email alerts
|

Stenting for colorectal cancer obstruction compared to surgery—a study of consecutive patients in a single institution

Abstract: Stenting can be safely performed with lower or similar complication rate and lower mortality rate compared to surgery and results in significantly shorter hospital stay. The results support stenting as the treatment of choice in patients with acute colonic obstruction, especially in disseminated disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
0
18
0
5
Order By: Relevance
“…When combined with bevacizumab, the risk of perforation increases [85]. Two recent studies found a similar complication rate in patients treated surgically and in those with stents [93,94]. Complications of SEMS use has been reported in patients with low volumes of hepatic replacement by metastases, as these patients risk outliving the stent's viability [87].…”
Section: Non-surgical Management Of Malignant Obstructionmentioning
confidence: 74%
See 2 more Smart Citations
“…When combined with bevacizumab, the risk of perforation increases [85]. Two recent studies found a similar complication rate in patients treated surgically and in those with stents [93,94]. Complications of SEMS use has been reported in patients with low volumes of hepatic replacement by metastases, as these patients risk outliving the stent's viability [87].…”
Section: Non-surgical Management Of Malignant Obstructionmentioning
confidence: 74%
“…Any treatment of colonic obstruction requires decompression to prevent colonic necrosis and perforation [85]. Stents can reach this endpoint without the risks associated with surgical trauma in high-risk patients [93]. Multiple studies have confirmed an improved outcome in patients treated with SEMSs as an elective rather than an emergency procedure.…”
Section: Non-surgical Management Of Malignant Obstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inzwischen zeigen mehrere direkte Vergleichsstudien zwischen Stentimplantation als «bridge to surgery» und Notfalloperation einerseits eindeutige Vorteile für die Stentgruppe [17,18], andererseits keine Vorteile für die Stentimplantation [19] bzw. in wenigen Serien eine Überlegenheit der operativen Therapie auch in der Notfallsituation [20,21].…”
Section: Literaturanalyse 1990–2012 Mit Schwerpunkt 2011/2012unclassified
“…Twenty-two patients (26.8%) had a complication of which 16 (19.5%) underwent urgent surgery for insufficient functioning of the stent; there were Significant complications of stent placement include perforation and bleeding and overall complication rates have been reported in approximately 4-40% of cases [6][7][8][9][10][11][12][13][14] . Of particular concern is perforation of the tumor, since it could lead to peritoneal tumor spill and dissemination of tumor cells [6,10,13,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%